Proyecto de Diseño Urbano Sectorial con Reconocimiento y Caracterización de los Espacios Logísticos en el Borde Urbano Mosquera y Fontibón (2022)
The present degree work is proposed to generate a sectoral urban scope, which consists of the design of the partial zonal plan of the Planadas neighborhood of the municipality of Mosquera and the Kassandra neighborhood of Bogotá, making use of concepts that are referenced from the study of authors who mention the urban edge and conurbation, exemplified in the city of Bogotá with the surrounding municipalities. Located in the municipality of Mosquera and UPZ No. 77 Zona Franca, Fontibón locality, city of Bogotá. The proposal manages to develop an urban design with a projectual scope in order to propose adequate spaces for the area based on the results of the territorial analysis